150 likes | 175 Views
Learn the rules of operations, including addition, subtraction, multiplication, and division. Practice with examples to master the BEDMAS order: Brackets, Exponents, Division, Multiplication, Addition, Subtraction. Ensure everyone gets the same correct answers!
E N D
Intro to Order of Operations(O-O-O) Math 7/8 COPY SLIDES WHEN YOU SEE THIS
Evaluate the following: • 3 x 6 + 2 x 10 • What is your answer?
Try Again! • Mr. and Mrs. Baker and their three children went to the movies. The cost for a child was $6.00 and the cost for an adult was $10.00. How much did the Baker family pay to go to the movies?
Taking Another Look …at $10 each …at $6 each • 3 x 6 + 2 x 10 = $38 3 children… 2 adults… added to
Order of Operations • When calculating equations with mixed operations(+, -, x, ) everyone must agree to follow the same rules; otherwise different people will get different answers. • Mathematicians have come up a set of rules. We call these rules, “Order of Operations”. • To help us remember the rules we use the word BEDMAS.
BEDMAS~Order of Operation RulesRead Left to Right You complete all operations inside the brackets first. • B ~ Brackets • E ~ Exponents • D ~ Division • M ~ Multiplication • A ~ Addition • S ~ Subtraction You do ALL adding and subtracting in the order they appear. You do not do any + or – until you have completed all x and You do ALL exponents in the order they appear. You do ALL x and in the order they appear.
Brackets • Brackets tell us that certain things belong together. What would you rather have?
Brackets • Brackets also tell us to do what is inside first.
What should be solved first? • 5 + 4 + 2 x 5 – 6 = • 5 + 4 + 2 x 5 – 6 = • 9 3 + 5 x 3 - 1 = • 9 3 + 5 x 3 - 1 = • 7 x 3 – (9 + 4) + 5 = • 7 x 3 – (9 + 4) + 5 =
What should be solved first? • 6 – 4 + 6 + 16 = • 6 – 4 + 6 + 16 = • (6 – 4) + (7 x 6) + 10 5 = • (6 – 4) + (7 x 6) + 10 5 = • 40 4 - (3 + 5 x 2 - 7) = • 40 4 - (3 + 5 x 2 - 7) =
What should be solved first? • 4 – 2 + 6 x 10 5 = • 4 – 2 + 6 x 10 5 = • 8 4 + (7 + 6) + 3 x 2 = • 8 4 + (7 + 6) + 3 x 2 = • (4 2 x 3 + 8) - 2 x 7 = • (4 2 x 3 + 8) - 2 x 7 =
Evaluate the following: • (6 + 3) x 2 – 4 + 3 x 2 • (30 + 8) – 3 x (4 + 6) • (4 + 6 x 2 – 9) x 2 – 10 • 6 + 3 x 2 3 x 5 + 8 2 – 4 x 2 • 2 x (4 – 3 + 2) • (8 – 3) + 5 x 2
Adding Brackets • 4 + 6 – 5 x 2 = 6 • 5 + 6 x 4 – 9 = 35 • 5 + 7 x 8 – 6 = 19 • 5 + 3 + 2 x 2 = 20
Adding Brackets • 7 + 4 x 3 – 1 = 15 • 3 + 5 + 4 x 2 = 21 • 7 x 3 – 1 + 4 = 16 • 26 – 5 x 4 2 = 3 • 4 + 3 x 3 – 1 = 14
Homework Questions • 2 x (3 x 7 ) – 5 • (15 – 5) + 5 x 3 • (6 x 23) – 10 • 5 + ( 6 + 33) • (10 + 9 – (4 x 7) 4)